The journey to elite success: a thirty-year longitudinal study of the career trajectories of top professional tennis players - Li, P.; De Bosscher, V.; Weissensteiner, J. R. (International Journal of Performance Analysis in Sport, 2018)
Learning from the career trajectories of the most successful elite players is central to informing effective strategies and long-term career planning to maximise player development and performance. This article examined the junior competition results and the performing age at major career milestones of top-level professional tennis players, utilising this information to forecast a player`s career peak ranking. Thirty years of longitudinal data which included 82 top 10 professional players between 2007 and 2017, were analysed. Gender and generational differences were compared. The results revealed that good performances at the highest junior level of competition was shown to be a critical precursor to eventual top-level professional success. It was revealed, however, that top 10 professional tennis players spent nearly 10 years from starting age to reaching an international junior level and another 10 years on average to achieve career peak ranking. Additionally, age at major career milestones was shown to be moderately correlated with a player`s career peak ranking, with 61% of the top one players correctly "predicted" to be top one players. The practical implications arising from these findings, specific to informing the career planning, prediction of professional success, monitoring and assessment of emerging tennis players, is discussed.